1995
DOI: 10.1111/j.1476-5381.1995.tb15132.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired endothelium‐dependent relaxation in isolated resistance arteries of spontaneously diabetic rats

Abstract: 1 Previous studies have shown that endothelium-dependent relaxation in the aorta of spontaneously diabetic bio bred rats (BB) is impaired. 2 We have investigated noradrenaline (NA) contractility, endothelium-dependent acetylcholine (ACh) and bradykinin (BK) relaxation, and endothelium-independent sodium nitroprusside (SNP) relaxation in mesenteric resistance arteries of recent onset BB rats and established insulin treated BB rats, compared to their age-matched non diabetic controls. 3 There was no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
3
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 70 publications
6
51
3
4
Order By: Relevance
“…Oxygen-derived free radicals play an important role in the occurrence of endothelium-dependent contractions in the basilar artery of the dog and the aorta of the spontaneously hypertensive rat Katusic et al, 1993;Yang et al, 2003aYang et al, , 2004aTang et al, 2007). Previous studies from our laboratory demonstrate that the calcium ionophore A23187 induces greater endothelium-dependent contractions in the femoral artery of diabetic rats than those of normoglycaemic animal (Shi et al, 2007), exemplifying the endothelial dysfunction caused by diabetes (Pieper and Gross, 1988;Heygate et al, 1995;Makimattila et al, 1996;Pieper et al, 1997;Vallejo et al, 2000). This prompted the investigation of the role of oxygen-derived free radicals in the endothelium-derived contracting factor-mediated responses of the femoral artery of rats with STZ-induced diabetes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Oxygen-derived free radicals play an important role in the occurrence of endothelium-dependent contractions in the basilar artery of the dog and the aorta of the spontaneously hypertensive rat Katusic et al, 1993;Yang et al, 2003aYang et al, , 2004aTang et al, 2007). Previous studies from our laboratory demonstrate that the calcium ionophore A23187 induces greater endothelium-dependent contractions in the femoral artery of diabetic rats than those of normoglycaemic animal (Shi et al, 2007), exemplifying the endothelial dysfunction caused by diabetes (Pieper and Gross, 1988;Heygate et al, 1995;Makimattila et al, 1996;Pieper et al, 1997;Vallejo et al, 2000). This prompted the investigation of the role of oxygen-derived free radicals in the endothelium-derived contracting factor-mediated responses of the femoral artery of rats with STZ-induced diabetes.…”
Section: Discussionmentioning
confidence: 89%
“…The effect of STZ-induced diabetes on nitric oxidemediated vasodilatation is still controversial; it has been reported as normal in the aorta (Head et al, 1987;Harris and MacLeod, 1988;Mulhern and Docherty, 1989), mesenteric artery (Harris and MacLeod, 1988) and femoral artery (Wigg et al, 2001), as blunted in aorta (Pieper et al, 1997;Vallejo et al, 2000), mesenteric artery (Heygate et al, 1995;Vallejo et al, 2000;Shi et al, 2007) and femoral artery (Shi et al, 2006) or augmented in aorta (Altan et al, 1989). The production of vasoconstrictor prostaglandins is augmented in diabetic animals (aorta , renal artery (Pflueger et al, 1999) and femoral artery (Shi et al, 2007)).…”
Section: Introductionmentioning
confidence: 99%
“…Production of superoxide anion inactivates NO (Marshall et al, 1988;Rubanyi & Vanhoutte, 1986;Kobayashi & Kamata, 2001) and dismutation of free radicals has generally (Pieper et al, 1996;Hattori et al, 1991;Kamata & Kobayashi, 1996) but not always (Heygate et al, 1995) been found to improve impaired endothelium-dependent relaxation in experimental models of diabetes. Indeed, we recently reported that NO is metabolized by O 2 7 to NO 3…”
Section: Discussionmentioning
confidence: 99%
“…There is now substantial evidence that endotheliumdependent vasodilation is abnormal in both conduit and resistance arteries of chemically induced experimental diabetic animals [Mayhan, 1989;Pieper and Gross, 1990;Mayhan et al, 1991;Diederich et al, 1994;Rosen et al, 1995;Taylor et al, 1995]. In two genetic models of IDDM, a similar impaired relaxation has been documented in the aorta [Durante et al, 1988;Pieper et al, 1996] and mesenteric arteries [Heygate et al, 1995;Lindsay et al, 1997] of diabetes-prone BB/W or BB/E rats. Similar results are reported for aorta and mesenteric arteries [Miyata et al, 1993] of the diabetes-prone WBN/Kob rat.…”
Section: Microvascular Dysfunction In Type-1 Diabetes Mellitusmentioning
confidence: 93%